Perancangan Video Promosi Aplikasi PT Aku Pintar Indonesia Dengan Menggunakan Flat Desain Serta Teknik Motion Graphic - Graciella Limputri; Jasson Prestiliano (APTIKOM SUMSEL, 2022)
Promotion is very important to introduce a product to target consumers and increase the number of users. Therefore, a promotional media was designed in the form of a video that provides information and introduces the Aku Pintar application using flat design and motion graphic techniques. The method used is a mixed method for data collection and testing of product results, as well as the use of a cyclic strategy. The design process starts from the idea & concept to the final result in the form of a promotional video using flat design and motion graphic techniques. The results achieved from this research are in the form of a promotional video entitled the Aku Pintar application, which is able to convey information about the services & features available in the Aku Pintar application and can be used as promotional media for companies.